Job satisfaction among Swedish police officers: The role of work-related stress, gender-based and sexual harassment - Rostami, Arian; Ghazinour, Mehdi; Burman, Monica; Hansson, Jonas (Frontiers in Public Health, 2022)
The aim of this cross-sectional study is to increase our understanding of job satisfaction in Swedish police officers by taking into account work-related stress, and sexual and gender-based harassment. Data were collected from 152 police officers working in vulnerable areas in Stockholm using sociodemographic questions, the Police Stress Identification Questionnaire (PSIQ), Sexual and gender-based harassment questions, and Job Descriptive Index (JDI). The obtained results indicated that male and female police officers reported the highest satisfaction in “people on your present job”. The lowest score of job satisfaction in both male and female police officers was related to “opportunity for promotion” and then “pay”. There were no significant differences between the subscales of job satisfaction between male and female police officers. The older and more experienced officers, the less satisfaction was reported in “job in general” and more satisfaction reported in “pay”. Comparing job satisfaction between patrol officers and those officers who worked in internal services showed police patrol officers have higher job satisfaction in “job in general”, “work in the present job”, “opportunity for promotion” and “supervision” compared to their counterparts in internal services. There were not any significant differences between the subscales of job satisfaction between male and female police officers. There was not any significant association between job satisfaction subscales and having experience of sexual or gender-based harassment. Among various subscales of police stressors, organizational stress was in negative relation with three domains of job satisfaction; “job in general”, “pay” and “supervision”. Also, hierarchical multiple regression analyses showed organizational stress was most often of predictive impact related to various job satisfaction domains in police officers.